Rumah Tuhan sebagai Rumah Keselamatan bagi Semua Orang: Pembacaan Poskolonial terhadap Yesaya 56:1-8 - Mangililo, Ira D. (Indonesian Journal of Theology, 2024)
This paper explores the existence of eunuchs in ancient Israel and the Israelites’ reception of them in the postexilic period. Using a postcolonial approach, this paper analyzes the ambiguity of the identities of foreigners and eunuchs, the liminal position they occupy in the Israelite community, the stereotypes they receive, and God’s actions to create a third space for them. The postcolonial reading of Isaiah 56:1-8 shows that there is an opportunity for foreigners and eunuchs who promise to keep the Sabbath and obey God’s covenant to live and become part of the Israelite community. Furthermore, Isaiah 56:1-8 also creates a third space for eunuchs where their dignity will be restored and their names will be immortalized forever. When connected to the Indonesian context, God’s initiative to bring marginalized and rejected eunuchs into the third space—a space of transformation that breaks down all oppressive binaries— becomes news of hope for sexual minority groups in Indonesia who have also experienced trauma and suffering. This interpretation calls for religious communities, including their leaders, to create a warm and loving home for others who are also part of God's family.